2017
DOI: 10.1097/01.aoa.0000521239.71749.7c
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Obstetric Anal Sphincter Injuries in a Modern Obstetric Population

Abstract: (Am J Obstet Gynecol. 2016;215(3):310.e1–e7) The main purpose of this nested case control study was to investigate a modern obstetric cohort in order to identify risk factors and develop prediction models for perineal lacerations and obstetric anal sphincter injuries (OASI, third and fourth degree lacerations) during vaginal delivery. In addition, this study also reevaluated the known risk factors in order to potentially identify new risk factors for any perineal laceration and OASI so as to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 2 publications
3
37
2
1
Order By: Relevance
“…Risk factors for severe laceration, including vaginal delivery with or without OVD, have been investigated in recent years. Birth weight is identified as one of the main factors and our analysis supported this theory . Previous reports have revealed that fetal head station and malrotation in OVD were strong risk factors and that reducing these factors would contribute to fewer severe lacerations .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Risk factors for severe laceration, including vaginal delivery with or without OVD, have been investigated in recent years. Birth weight is identified as one of the main factors and our analysis supported this theory . Previous reports have revealed that fetal head station and malrotation in OVD were strong risk factors and that reducing these factors would contribute to fewer severe lacerations .…”
Section: Discussionsupporting
confidence: 82%
“…Gossett et al reported that simulation‐based forceps delivery training is associated with a significant reduction (22%) in severe perineal lacerations . Risk factors of severe laceration have been investigated over the years, including vaginal delivery with or without OVD . However, a PubMed search for articles using the key words “simulation training” and “obstetric forceps” limited to the English language identified only 13 reports.…”
Section: Introductionmentioning
confidence: 99%
“…2 Furthermore, equating vaginal delivery with optimal outcome is simplistic, as complicated vaginal deliveries are associated to damage to the pelvic floor and anal sphincter ruptures. 3,4 No choice is risk neutral and cesarean deliveries at low fetal head station are also associated with risk of maternal and fetal complications. [5][6][7] So, the goal of obstetric care in the second stage of labor must be to avoid cesarean deliveries where assisted or spontaneous vaginal delivery is likely to be safe and achievable.…”
Section: Introductionmentioning
confidence: 99%
“…Obstetric anal sphincter injuries (OASIS) can complicate up to 6% of births [1][2][3][4][5][6][7][8] and are a major contributor to preventable maternal morbidity. 9 OASIS have been linked with a number of long-term complications such as faecal incontinence, urinary incontinence, perineal pain, dyspareunia, embarrassment and low self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…9 OASIS have been linked with a number of long-term complications such as faecal incontinence, urinary incontinence, perineal pain, dyspareunia, embarrassment and low self-esteem. 10 Instrumental delivery, increasing birthweight and prolonged second stage are all recognised risk factors for OASIS; 6,8,[11][12][13][14] however, the role of ethnicity remains uncertain.…”
Section: Introductionmentioning
confidence: 99%